2002
DOI: 10.1177/106689690201000207
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Chronic Lymphocytic Thyroiditis and Thyroid Tumors

Abstract: An association between lymphocytic thyroiditis and thyroid papillary carcinoma is still controversial. To assess the relationship, a histopathologic analysis of surgically resected thyroid tumors together with the frequency and severity of chronic lymphocytic infiltration of the thyroid among patients with follicular adenoma, follicular carcinoma, and papillary carcinoma was performed. The prevalence of lymphocytic infiltrate, which is indicative of autoimmune thyroiditis, was significantly higher in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 16 publications
0
82
1
3
Order By: Relevance
“…RET/PTC fusion proteins, like RP3, may be directly responsible for provoking the chronic inflammatory disease coincident with cancer in thyroid disease patients. This is of particular interest since the frequency of thyroiditis in thyroid cancer is approximately 30% (Braverman and Utiger, 1995;Kebebew et al, 2001) and can be as high as 50% in some patients (Tamimi, 2002). Furthermore, thyroiditis may become a common malady as we age, since an estimated 6.6% of autopsies show pathological evidence of thyroiditis in normal (euthyroid) individuals (Fleischmann and Hardmeier, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RET/PTC fusion proteins, like RP3, may be directly responsible for provoking the chronic inflammatory disease coincident with cancer in thyroid disease patients. This is of particular interest since the frequency of thyroiditis in thyroid cancer is approximately 30% (Braverman and Utiger, 1995;Kebebew et al, 2001) and can be as high as 50% in some patients (Tamimi, 2002). Furthermore, thyroiditis may become a common malady as we age, since an estimated 6.6% of autopsies show pathological evidence of thyroiditis in normal (euthyroid) individuals (Fleischmann and Hardmeier, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This association was shown to correspond to a favorable clinical outcome in patients with infrequent tumor recurrence, more differentiated tumors and lower mortality rates (Matsubayashi et al, 1995;Loh et al, 1999;Tamimi, 2002). While the origins of papillary thyroid carcinoma-associated lymphocytic thyroiditis are unknown, genetic analysis of papillary thyroid carcinomas has shown that specific chromosomal rearrangements of the RET/PTC gene family are prevalent (Jhiang, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this notion, 10-40% of patients diagnosed with Hashimoto's thyroiditis (HT) may show evidence of concurrent thyroid carcinoma (Dailey et al, 1955;Ott et al, 1987). Although the role of these immune infiltrates is uncertain, clinical studies have shown that patients with papillary thyroid carcinoma (PTC) that present with thyroiditis (PTC/ HT) have a better clinical outcome than patients diagnosed with PTC alone (Matsubayashi et al, 1995;Loh et al, 1999;Tamimi, 2002). Understanding the molecular mechanisms that distinguish PTC from PTC/ HT will be critical if we are to take advantage of the anticancer responses that likely explain the difference between these two pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…From a histological perspective, Tamimi et al assessed the prevalence and severity of thyroiditis among three types of surgically resected thyroid tumors and found a significantly higher rate of lymphocytic infiltrate in patients with PTC [14]. Again PTC with concurrent HT is associated with female gender, young age, less aggressive disease such as small tumor size, less frequent capsular invasion and nodal metastasis, and better prognosis [15,16].…”
Section: Hashimoto's Thyroiditis and Papillary Thyroid Cancermentioning
confidence: 99%
“…Again PTC with concurrent HT is associated with female gender, young age, less aggressive disease such as small tumor size, less frequent capsular invasion and nodal metastasis, and better prognosis [15,16]. Furthermore, these patients are also less likely to develop recurrence and have a higher survival rate [14,15,17,18], mostly explained by the fact that the autoimmune response to thyroid specific antigens in patients with HT may be involved in the destruction of cancer cells expressing thyroid specific antigen in PTC. However, it remains unclear whether or not the presence of HT affects the biologic behavior of PTC, although the association between HT and PTC has been reported in many studies [9,15,18,23].…”
Section: Hashimoto's Thyroiditis and Papillary Thyroid Cancermentioning
confidence: 99%